2018
DOI: 10.1177/1049909118794149
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Initiatives to Reduce Mortality: An Opportunity to Engage Palliative Care and Improve Advance Care Planning

Abstract: Clinicians who participated in an initiative to reduce AMI mortality highlighted the challenges associated with decision-making regarding interventions, systems for documenting patient goals of care, and broader engagement with palliative care. Quality improvement initiatives focused on mortality may offer a meaningful and feasible opportunity for engaging palliative care. Primary palliative care training is needed to improve discussions about patient and family goals of care near the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The physicians of our Department believe their role is to cure and to offer therapeutic solutions, and they would gladly have someone else take care of the patients who are dying and can no longer be saved, and who are, as such, no longer candidates for the highly active and interventional opportunities the cardiologist can offer. This finding is in line with the findings of the qualitative study by Flieger et al, where respondents indicated that a lot of cardiology professionals are afraid of palliative care, and that cardiologists "don't believe in it" [14]. The authors relate this rejection of palliative care to the tendency towards intervention among cardiologists.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The physicians of our Department believe their role is to cure and to offer therapeutic solutions, and they would gladly have someone else take care of the patients who are dying and can no longer be saved, and who are, as such, no longer candidates for the highly active and interventional opportunities the cardiologist can offer. This finding is in line with the findings of the qualitative study by Flieger et al, where respondents indicated that a lot of cardiology professionals are afraid of palliative care, and that cardiologists "don't believe in it" [14]. The authors relate this rejection of palliative care to the tendency towards intervention among cardiologists.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, they describe a therapeutic approach akin to a conveyor belt of care: once the patient is admitted and steps onto that conveyor belt, they are moved along as the physician proposes one therapy, intervention or device after another, until all possibilities have been exhausted. Indeed, in a secondary analysis of qualitative data collected through the Leadership Saves Lives initiative, Flieger et al described this phenomenon as the "power of momentum", whereby once the patient presents with an acute need, that increases the likelihood of intervention [14]. With the outstanding progress in medical and device therapy in recent years, there is now a very large choice of therapies available, and thus, for a long time during the course of disease, physicians can offer a new therapy every time the previous one has failed.…”
Section: Discussionmentioning
confidence: 99%
“…We will systematically search for disconfirming evidence [84], interview multiple participants in each health system for triangulation [85], and maintain a detailed audit trail to document analytic decisions [76]. To our knowledge, this will be one of the largest longitudinal qualitative data sets in the country [83], and could support sub-investigations on the nature of structural racism and health [31,86].…”
Section: Data Collectionmentioning
confidence: 99%
“…8 Furthermore, hospitals demonstrating culture change provided important insights into enhancing the role of pharmacists in care of patients with AMI, 9 as well as opportunities to engage palliative care and improve advance care planning for patients with AMI. 10 Despite the potential impact of complex interventions such as LSL, reports in the peer-reviewed literature often lack description of the intervention design process, and omit the detail required to allow for replication of the intervention for further testing, adoption and adaptation of the intervention for broader impact, or synthesis of evidence across studies. [11][12][13][14] The protocol specifying the theoretical framework and central elements of the study's intervention design, as well as the study's evaluation methods, has been previously published, 5 as have papers reporting validation of the organisational culture measure 15 and results of the intervention on organisational culture and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Furthermore, hospitals demonstrating culture change provided important insights into enhancing the role of pharmacists in care of patients with AMI, 9 as well as opportunities to engage palliative care and improve advance care planning for patients with AMI. 10 …”
Section: Introductionmentioning
confidence: 99%